Measuring Intuitionistic Fuzzy Set Relative membership: An analytical approach: Exploring the Applications and Properties of Intuitionistic Fuzzy Set Theory (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The interesting IFS (Intuitionistic Fuzzy Set) theory, introduced by K. T. Atanassov, is a tool forproblem-solving. The IFS effectively broadens Zadeh's imprecise set. Recently, the IFS theory has beenapplied to many different domains, such as logic programming, decision making problems, and medicaldiagnoses.Fuzzy sets can be defined as For any space S, there exists a fuzzy set F specified as a nonemptycollection of 2-tuple members. Each constituent of an IFS is a 4-tuple consisting of a membershipdegree, reluctance degree, and non-membership degree, and the collection is defined in a domain ofspeech where u_rS[0,1]. The degree of hesitation u_r (g)[0,1] can play a role in participation, in nonmembership,or in both. The following illustrations illustrate the aforementioned three levels.